REGIONAL CHARACTERISTICS, PRINCIPLES AND PERSPECTIVES OF EUROPE'S EXTERNAL ENERGY SUPPLY (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
In terms of content and direction perspectives, the paper is related to regional energy studies, which are interdisciplinary in nature, including geographical, geopolitical, economic, environmental and other directions. In the theoretical part, the main substantive issues and features of regional energy studies, their role and significance in the context of energy security and energy policy were presented. Based on statistical data analysis, the current state of external energy supply, problems, regional trends and features of European (including both EU and non-EU members) were presented and summarized. Taking into account the geopolitical aspects of ensuring Europe's energy security, the main directions of the U.S. and Russian involvement in this field and their regional features were also discussed. Special attention was paid to the spatial expansion of energy imports from foreign markets and continuous regional energy cooperation.
Keywords: regional energy studies; Europe; external energy supply; regional peculiarities